Thermodynamic analysis of a gamma-configuration stirling engine - Munir Afnan, Mukhtar; R. A., Bakar; Mohd Farid, Zainudin (Akademi Baru, 2021)
Stirling engine is seen as a viable alternative to the conventional power generator due to its special capability to work with externally supplied heat sources which make the renewable and waste energy can be applied directly for a green energy production. Researchers from institutions and industries around the world have put their efforts in developing Stirling engine from numerical analysis to prototype development. In this paper, a simple thermodynamic analysis has been done on a proposed slider-crank gamma-configuration Stirling engine. The purpose of this analysis is to investigate the engine working capability of the proposed design prior to its prototype development. The analysis is done based on modified Schmidt ideal adiabatic model. The expansion and compression space temperature were set as 573K and 300K, respectively and air was used as the working fluid. With the assumed speed of 300rpm and running at atmospheric pressure, from the analysis, the proposed engine is predicted to produce 33.41W of power output. Additional to that, the selection of 90° phase angle also has been verified and the relationship between the temperature difference and produced power output also has been investigated. It is found that with 400K increment of the temperature difference between expansion and compression space, the produced power output can be increased by 94.93%. From the analysis, it showed that the proposed design can be proceeded for the prototype development.